2012
DOI: 10.1190/geo2011-0067.1
|View full text |Cite
|
Sign up to set email alerts
|

An improved vacuum formulation for 2D finite-difference modeling of Rayleigh waves including surface topography and internal discontinuities

Abstract: Rayleigh waves are generated along the free surface and their propagation can be strongly influenced by surface topography. Modeling of Rayleigh waves in the near surface in the presence of topography is fundamental to the study of surface waves in environmental and engineering geophysics. For simulation of Rayleigh waves, the traction-free boundary condition needs to be satisfied on the free surface. A vacuum formulation naturally incorporates surface topography in finite-difference (FD) modeling by treating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…For elastic wave propagation, Bartel et al (2000) find that some smoothing of the extreme density contrast is required for numerical stability. Boore (1972), Robertsson (1996), Mittet (2002), Bohlen and Saenger (2006), and Zeng et al (2012) consider variants of the vacuum approach. Unfortunately, the loss of accuracy can become significant: Numerical experiments with a higher order finite-difference scheme for the acoustic wave equation indicate that the numerical error increases to only the first order in space (Zhebel et al, 2014) in case of a smoothed density contrast.…”
Section: Introductionmentioning
confidence: 99%
“…For elastic wave propagation, Bartel et al (2000) find that some smoothing of the extreme density contrast is required for numerical stability. Boore (1972), Robertsson (1996), Mittet (2002), Bohlen and Saenger (2006), and Zeng et al (2012) consider variants of the vacuum approach. Unfortunately, the loss of accuracy can become significant: Numerical experiments with a higher order finite-difference scheme for the acoustic wave equation indicate that the numerical error increases to only the first order in space (Zhebel et al, 2014) in case of a smoothed density contrast.…”
Section: Introductionmentioning
confidence: 99%
“…3). We found that the second-order-accurate [71] and fourth-order-accurate [83] spatial finite difference operators were both stable and suitable for our purposes. We used the second-orderaccurate operator because it is computationally simpler.…”
Section: A the Finite-difference Time-domain (Fdtd) Methods For The Ementioning
confidence: 94%
“…For accuracy and stability, a half-grid-cell-thick fictitious layer of material is added around the structure to ease the transition from the material to vacuum [83]. Fixed BCs are simpler to implement: we force v = 0 on the surface.…”
Section: A the Finite-difference Time-domain (Fdtd) Methods For The Ementioning
confidence: 99%
“…We run the case both with the vacuum formulation (Robertsson, 1996;Zeng et al, 2012) and with the mimetic approach described here.…”
Section: Examplementioning
confidence: 99%